Improvements in hydrogen production from methane dry reforming on filament-shaped mesoporous alumina-supported cobalt nanocatalyst - Tran, Ngoc Thang; Pham, Thong Le Minh; Nguyen, Trinh Duy; Cuong, Nguyen Van; Siang, Tan Ji; Phuong, Pham T.T.; A.A., Jalil; Truong, Quang Duc; Sumaiya, Zainal Abidin; Hagos, Ftwi Y.; Sonil, Nanda; N. Vo, Dai-Viet (Elsevier Ltd, 2021)
The mesoporous gamma-alumina (g-Al2O3) synthesized via evaporation-induced self-assembly method (EISA) using inorganic salt, Al(NO3)3$9H2O precursor and water-ethanol solvent mixture was implemented as a support for Co catalyst in methane dry reforming at 973e1073 K under 1 atm. The g-Al2O3 support possessed filament-shaped morphology with surface area of 173.4 m2 g1 and cobalt nanoparticles were successfully dispersed on support with small crystallite size of 7.8 nm. The stability of 10%Co/Al2O3 was evident for CH4 and CO2 conversions at 1023 and 1073 K. CH4 conversion could reach to 76.2% while 81.6% was observed for CO2 conversion at 1073 K. Although graphitic and amorphous carbons were unavoidably formed on used catalyst, 10%Co/Al2O3 exhibited an outstanding performance comparable to noble metals with the desired ratio of H2/CO for downstream Fischer-Tropsch process.